The relationship between dietary habits and menstruation problems in women: a cross-sectional study - Hatice Kübra Barcın Güzeldere; Emine Hilal Efendioğlu; Sümeyye Mutlu; Havva Nur Esen; Gamze Nur Karaca; Beyzanur Çağırdar (BMC, 2024)
Abstract Background Nutrition is important to the management and relief of the symptoms in menstrual disorders. This study aims to investigate the relationship between menstrual disorders and specific foods and nutrient intake in women. Methods Five-hundred-nine menstruating women participated in the study. The questionnaire form was created by the researchers via Google Forms and distributed in online applications (WhatsApp, Instagram etc.). The questionnaire consists of 5 sections, including demographic data, declared anthropometric measurements (height (m or cm), weight (g or kg)), questions about eating habits, menstruation status, and 24-hour food consumption. Statistical analysis was made with SPSS 23; nutrient analysis of food consumption was made using BeBiS 9.0. Results It was found that the body mass index (BMI) of healthy participants was higher than women with menstrual disorders. Women with menstrual disorders have lower intake of protein, vitamin K, vitamin B3, vitamin B5 and sodium compared with healthy women. All participants have a higher intake of vitamin B3, sodium, phosphorus, and manganese, and have a lower intake of other nutrients compared with the national adequate intake. Conclusion Our findings showed that women with menstrual disorders consume more high-sugar food/beverages and have inadequate nutrients intake.